Does Literacy Moderate the Relationship between Age of Migration and Cognitive Change: Results from the Washington Heights-Inwood Community Aging Project (WHICAP). (30th August 2019) - Carrión, C I; Arias, F; Diaz-Santos, M; Levy, S-A; Hill-Jarrett, T G; Avila, J; Jones, R; Rivera Mindt, M; Arce, M; Schupf, N; Mayeux, R; Manly, J
Abstract: Objective: The "healthy immigrant effect" pertains to findings that Hispanics/Latinos born outside of the US tend to be physically and emotionally healthier than individuals born in the US. However, immigrant Latino groups residing in the US have higher incidences of dementia (Tang et al., 2001). Sex/gender and years of education have been found to moderate the relationship between age of migration and cognitive functioning among immigrants born in Mexico (Garcia et al., 2017; Hill et al., 2012). While years of education has been the focus of many studies, literacy (ability to read/write) has been less frequently explored as a moderator of age of migration and cognitive change. We investigated the effect of age of migration on cognitive trajectory in a diverse Latino population and explored whether literacy influences the association between age of immigration and cognitive change. We hypothesize that literacy (ability to read/write) will buffer the effects of age of migration on cognitive (memory, language, motor speed, visuospatial) trajectory. Participants and Method: Age at baseline, English fluency, country of birth, sex/gender, and years of education were included as time-invariant covariates and literacy was tested as a moderator via multiple group modeling. Results: Results show that age of migration is marginally and inversely associated with baseline cognitive performance (p < .01). Thus, individuals who immigrated at an older age had lower baseline cognitive scores than their counterparts. Age of migration was not associated with cognitive change. Independent of covariates, literacy did not buffer the negative effects of later age at migration on cognitive function. Conclusions: Results suggest that literacy confers a small advantage in premorbid cognition, but does not protect against cognitive decline over time. These findings also suggest that adults who immigrate at an older age present with lower cognitive scores at baseline, but do not experience faster rates of cognitive change. References: Tang, M. X., Cross, P., Andrews, H., Jacobs, D. M., Small, S., Bell, K., ... & Mayeux, R. (2001). Incidence of AD in African-Americans, Caribbean Hispanics, and Caucasians in northern Manhattan. Neurology, 56, 49-56. Garcia, M. A., Reyes, A. M., Downer, B., Saenz, J. L., Samper-Ternent, R. A., & Raji, M. (2018). Age of migration and the incidence of cognitive impairment: A cohort study of elder Mexican-Americans. Innovation in aging, 1, igx037. https://doi.org/10.1093/geroni/igx037 . Hill, T. D., Angel, J. L., Balistreri, K. S., & Herrera, A. P. (2012). Immigrant Status and Cognitive Functioning in Late Life: An Examination of Gender Variations in the Healthy Immigrant Effect. Social Science & Medicine (1982), 75, 2076–2084. http://doi.org/10.1016/j.socscimed.2012.04.005 .